Designing and analyzing an electric energy storage system based on reversible solid oxide cells. (1st March 2018) - Perna, Alessandra; Minutillo, Mariagiovanna; Jannelli, Elio
Highlights: A hydrogen-based electric energy storage plant configuration is proposed and analyzed. The electric energy storage is based on reversible solid oxide cell technology. The system design has been performed by thermal and electrochemical modeling. The Balance of Plant sections are designed to avoid the external heat supply. The system stores and uses the renewable energy with high roundtrip efficiency (60%). Abstract: The Reversible Solid Oxide Cell (ReSOC), operating under electrolysis and fuel cell modes, is a promising technology that, thanks to high efficiency and fuel flexibility, can be applied in the development of Electric Energy Storage (EES) systems. Several critical issues are required to be addressed, which are specific to ReSOC, such as oxidant electrode performance and reversibility, set of materials, cell/stack design and operating parameters suitable for reversible operation. Moreover, the optimal system design, to demonstrate the feasibility of the technology as well as the Balance of Plant (BoP) components at high operating temperatures, are also challenging factors. Therefore, the objective of this work is to propose an HEES (Hydrogen-based Electric Energy Storage) system for distributed scale energy storage applications (100–200 kW) by taking into account some of these challenging issues. The proposed system consists of (i) the BoP section needed for the energy storage, (ii) the ReSOC module operating in reversible mode, (iii) the BoP section needed for the energy production. In order to guarantee a competitive roundtrip efficiency, the design of the solid oxide cell unit and of the supporting auxiliary systems (BoP components) has been performed without external heat sources for the heating of feeding streams and for the thermal requirements of the ReSOC during its operation in the electrolysis mode. The study has been carried out by developing a steady-state thermo-electrochemical model that has been built with a modular architecture. The model, validated by means of experimental data, has been used to assist the system designing and the thermal management optimization to ensure high performances from electric and thermal points of view. Results highlight that the proposed system is able to store and use the renewable energy with a roundtrip efficiency of 60%. Moreover, thanks to the optimized thermal integration, additional heat is available for cogeneration purpose, with a cogeneration efficiency of 91%.